CREATING PUBLIC SERVICES BASED ON LANGUAGE POLITENESS: AN ANALYSIS OF EFFECTIVE INDONESIAN LANGUAGE - Aziz, Zeidtry Maulana; Anwar, Miftahulkhairah; Murtadho, Fathiaty (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This study aims to analyze the application of language politeness in public services during dialogical patrols. This study uses a descriptive qualitative method to understand how language politeness strategies are applied in interactions between police and society, based on Geoffrey Leech's politeness theory. Data were collected through direct observation of police dialogue with the community, which was analyzed to identify the realization of Indonesian politeness, politeness violations and how the construct of Indonesian politeness is constructed. The results showed that the maximum of Sympathy was the most dominant with a percentage of 25.68%, followed by the maxim of Praise (19.98%), Approval (17.16%), Wisdom (17.16%), Generosity (11.41%), and Humility (8.55%). Although there are some violations of politeness, such as positive (0.9%) and negative (1.8%) disrespect, police officers generally try to maintain polite communication and support positive relationships with the community. This study concludes that the application of language politeness by the police in dialogical patrols plays an important role in building positive relationships with the community and increasing public trust.